Comparison Between The Experimentally and Numerically Modeled and Simulated Kinetic Parameters Corresponding to Michaelis-Menten Equation for NADH Sensors Based on Polymeric Phenothiazine Modified Electrodes - LIGIA UNGURESAN*, MIHAELA; MARIA GLIGOR†, DELIA (Asian Journal of Chemistry, 2009)
The paper presents a comparison between the experimentally and numerical modeled and simulated kinetic parameters (Michaelis-Menten constant, KM and Imax) obtained by fitting the Michaelis-Menten equation, for NADH amperometric measurements at electrodes modified with polymeric phenothiazines. The modified electrodes were obtained by two different approaches: (i) adsorption of the poly-phenothiazine formaldehyde (PPF) on graphite electrodes (G/PPF) and (ii) electro polymerization of bis-phenothiazin-3-yl-methane (BPhM) on glassy carbon electrodes (GC/poly-BPhM). It was obtained a good correlation of the simulated kinetic parameters with the experimental values. GC/poly-BPhM electrodes present a higher sensitivity for NADH detection than G/PPF electrodes, at an applied potential of +200 mV vs. SCE and +50 mV vs. SCE, respectively.